Adjuvant intraperitoneal chemotherapy for the treatment of colorectal cancer at risk for peritoneal carcinomatosis: a systematic review. (4th July 2018) - Feingold, Paul L.; Klemen, Nicholas D.; Kwong, Mei Li M.; Hashimoto, Barry; Rudloff, Udo
Abstract: Background: The peritoneal surface is the second most common site of disease recurrence, after the liver, following definitive surgery for colorectal cancer. Adjuvant intraperitoneal (IP) chemotherapy delivered at time of surgical resection has the potential to delay or prevent future spread to the peritoneal surface and improve clinical outcome. The exact role of adjuvant IP chemotherapy in colorectal cancer, including its associated morbidity and mortality, is not well defined. Study design: Systematic review and pooled random effect analysis of comparative trials examining the addition of adjuvant IP chemotherapy compared to surgery alone in colorectal cancer. The primary outcome was overall survival, and the secondary outcomes were of post-operative morbidity and mortality. Results: In nine colorectal cancer studies identified, seven were two-arm trials comparing adjuvant IP chemotherapy to surgery alone. Of these, four trials had outcome reporting and met criteria that allowed inclusion into a random effects model. Heterogeneity was measured by Cochran's Q -test ( Q  = 13.9; p  = 0.01) and random effect models were utilised. Pooling eligible trials together revealed a 0.55 odds ratio of death associated with the administration of IP chemotherapy compared to surgery alone (CI = 0.31, 0.98; p  = 0.04). Trials selecting patients at elevated risk for the development of peritoneal carcinomatosis by clinicopathological biomarkers for administration of adjuvant IP chemotherapy reported more favourable overall outcomes. There was no increase in mortalities or IP chemotherapy-related abdominal complication rates among patients undergoing IP chemotherapy (OR = 1.4; CI = 0.52, 3.8; p  = 0.5). Conclusions: This systematic review supports the use of adjuvant IP chemotherapy in resectable colorectal cancer at risk for peritoneal spread. Future trials should seek to standardise inclusion criteria and IP chemotherapy modalities to better define the role of this treatment in patients with resectable colorectal cancer.